2019
DOI: 10.1186/s12866-019-1511-x
|View full text |Cite
|
Sign up to set email alerts
|

PgFur participates differentially in expression of virulence factors in more virulent A7436 and less virulent ATCC 33277 Porphyromonas gingivalis strains

Abstract: Background Porphyromonas gingivalis is considered a keystone pathogen responsible for chronic periodontitis. Although several virulence factors produced by this bacterium are quite well characterized, very little is known about regulatory mechanisms that allow different strains of P. gingivalis to efficiently survive in the hostile environment of the oral cavity, a typical habitat characterized by low iron and heme concentrations. The aim of this study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 86 publications
(101 reference statements)
1
36
1
Order By: Relevance
“…Recently, we have shown that P. gingivalis ferric uptake regulator homolog (PgFur) is an important transcription factor, regulating genes involved in interaction with host cells and other periodontopathogens [13,16]. A P. gingivalis mutant strain lacking a pgfur gene showed reduced tolerance to H 2 O 2 and was more sensitive to air exposure, although we did not observe regulation of typical genes responsible for the oxidative stress response [13,16].…”
Section: Introductioncontrasting
confidence: 56%
See 4 more Smart Citations
“…Recently, we have shown that P. gingivalis ferric uptake regulator homolog (PgFur) is an important transcription factor, regulating genes involved in interaction with host cells and other periodontopathogens [13,16]. A P. gingivalis mutant strain lacking a pgfur gene showed reduced tolerance to H 2 O 2 and was more sensitive to air exposure, although we did not observe regulation of typical genes responsible for the oxidative stress response [13,16].…”
Section: Introductioncontrasting
confidence: 56%
“…Prevotella intermedia strain 17 (GenBank: CP003502.1 and CP003503.1) and Tannerella forsythia (ATCC 43037) were maintained as described previously [37]. Streptococcus gordonii (ATCC 10558) was grown in TSB agar or liquid medium (5% TBS) under an increased concentration of CO 2 using the Atmosphere generation system (Thermo Scientific, Waltham, MA, USA) as reported previously [16].…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 3 more Smart Citations